Patterns of daily prayer in Second Temple period Judaism - Penner, Jeremy. (Studies on the Texts of the Desert of Judah, 2012)
In Patterns of Daily Prayer in Second Temple Period Judaism , Jeremy Penner seeks to uncover the historical and social processes that underlie the origins and development of Jewish daily prayer practices, particularly the establishment of set times for daily prayer. Since daily prayer lacks explicit biblical warrant, this book seeks to explain how this custom was legitimized as divinely inspired. The importance of daily prayer was understood and experienced within a range of literary and social contexts, and thus different exegetical and etiological strategies develop at this time to legitimize its practice. In some cases daily prayer was coordinated with, and made analogous to, daily cultic sacrifice, in other cases, daily prayer was legitimized by identifying the origins of the practice in sacred scripture. Lastly, in some contexts daily prayer was coordinated with the cycles of celestial bodies in the heavens.